MEDIA PEMBELAJARAN CUTTING ENGINE SISTEM TRANSMISI SEPEDA MOTOR MANUAL TIPE CUB - Sunarto Hidayat; Haris Abizar; Sulaeman Deni Ramdani (JURNAL PENDIDIKAN TEKNIK MESIN, 2021)
This paper reports a study that examines the manufacture and feasibility of cutting engine learning media. learning in related subjects. The research was conducted using the Research and Development (R&D) method of the Borg and Gall development model. The subjects of this study consisted of 3 material experts, 3 media experts, and 21 college students. This research produces Learning Media products that have a choice of operating modes (automatic or mechanical) as well as visualization transfer features that make this product a flexible character learning medium. The feasibility of learning media based on the validation results from material experts and media experts shows that this learning media is suitable for use in learning. The average result of the questionnaire that has been obtained from media experts shows a percentage of 78% in the "Good" category. The average results of media experts show a percentage of 86.60% in the "Very Good" category and the average for the questionnaire that has been obtained from users shows a percentage of 87.20% in the "Very Good" category.